Alteration of fecal tryptophan metabolism correlates with shifted microbiota and may be involved in pathogenesis of colorectal cancer - Sun, Xi-Zhen; Zhao, Dong-Yan; Zhou, Yuan-Chen; Wang, Qian-Qian; Qin, Geng; Yao, Shu-Kun (World journal of gastroenterology : WJG, 2020)
Gut tryptophan (Trp) metabolites are produced by microbiota and/or host metabolism. Some of them have been proven to promote or inhibit colorectal cancer (CRC) and animal models. We hypothesized that there is an alteration of gut Trp metabolism mediated by microbiota and that it might be involved in the pathogenesis of cancer in patients with CRC. To investigate the features of Trp metabolism in CRC and the correlation between fecal Trp metabolites and gut microbiota. Seventy-nine patients with colorectal neoplastic lesions (33 with colon adenoma and 46 with sporadic CRC) and 38 healthy controls (HCs) meeting the inclusion and exclusion criteria were included in the study. Their demographic and clinical features were collected. Fecal Trp, kynurenine (KYN), and indoles (metabolites of Trp metabolized by gut microbiota) were examined by ultraperformance liquid chromatography coupled to tandem mass spectrometry. Gut barrier marker and indoleamine 2,3-dioxygenase 1 ( ) mRNA were analyzed by quantitative real-time polymerase chain reaction. Zonula occludens-1 (ZO-1) protein expression was analyzed by immunohistochemistry. The gut microbiota was detected by 16S ribosomal RNA gene sequencing. Correlations between fecal metabolites and other parameters were examined in all patients. The absolute concentration of KYN [1.51 (0.70, 3.46) nmol/g 0.81 (0.64, 1.57) nmol/g, = 0.036] and the ratio of KYN to Trp [7.39 (4.12, 11.72) × 10 5.23 (1.86, 7.99) × 10 , = 0.032] were increased in the feces of patients with CRC compared to HCs, while the indoles to Trp ratio was decreased [1.34 (0.70, 2.63) 2.46 (1.25, 4.10), = 0.029]. The relative mRNA levels in patients with CRC (0.27 ± 0.24) were significantly lower than those in HCs (1.00 ± 0.31) ( < 0.001), and the relative mRNA levels in patients with CRC [1.65 (0.47-2.46)] were increased ( = 0.035). mRNA levels were positively associated with the KYN/Trp ratio ( = 0.327, = 0.003). ZO-1 mRNA and protein levels were positively correlated with the indoles/Trp ratio ( = 0.035 and = 0.009, respectively). In addition, the genera (Actinobacteria) and (Bacteroidetes) and members of the phylum Firmicutes ( and ) decreased in CRC and exhibited a positive correlation with indoles in all subjects. Alteration of fecal Trp metabolism mediated by microbiota is associated with intestinal barrier function and tissue Trp metabolism, and may be involved in the pathogenesis of CRC.